Dystopian fiction east and west : universe of terror and trial - Gottlieb, Erika (McGill-Queen's University Press, 2001)
"Dystopian Fiction East and West suggests that the utopian pursuit of "the best of all possible worlds" is driven less by the search for happiness than by a determined faith in justice. Conversely, the world of dystopian fiction presents us with a society where the ruling elite deliberately subverts justice. In fact, twentieth-century dystopian fiction can be seen as a protest against the totalitarian superstate as the "worst of all possible worlds," a universe of terror and rigged trials." "Erika Gottlieb explores a selection of about thirty works in the dystopian genre from East and Central Europe between 1920 and 1991 in the USSR and between 1948 and 1989 in Poland, Hungary, and Czechoslovakia. Written about and under totalitarian dictatorship, in these countries dystopian fiction does not take us into a hypothetical future; instead the writer assumes the role of witness protesting against the "worst of all possible worlds" of terror and trial in a world that is but should not be."--Jacket